2012
DOI: 10.1167/iovs.11-9244
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Multiple Cytokines in the Vitreous of Patients with Sarcoid Uveitis

Abstract: Patients with ocular sarcoidosis had elevated levels of proinflammatory cytokines in vitreous fluids. Different cytokines might contribute to different stages of macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…In the present study, although there was no significant difference in vitreous IL-4 level between the ocular sarcoidosis group and the idiopathic ERM group, vitreous levels of IL-6, IL-10, IFN-c, and TNFa were significantly elevated in the ocular sarcoidosis group compared with the idiopathic ERM group (Fig. 5), consistent with the report of Nagata et al 40 We previously demonstrated that serum CXCL9 and CXCL10 levels are markedly augmented in patients with ocular sarcoidosis compared with healthy subjects. These results indicate a role of CXCL9 and CXCL10 in the mechanisms that account for migration of CXCR3-expressing activated Th1 cells to the eye.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, although there was no significant difference in vitreous IL-4 level between the ocular sarcoidosis group and the idiopathic ERM group, vitreous levels of IL-6, IL-10, IFN-c, and TNFa were significantly elevated in the ocular sarcoidosis group compared with the idiopathic ERM group (Fig. 5), consistent with the report of Nagata et al 40 We previously demonstrated that serum CXCL9 and CXCL10 levels are markedly augmented in patients with ocular sarcoidosis compared with healthy subjects. These results indicate a role of CXCL9 and CXCL10 in the mechanisms that account for migration of CXCR3-expressing activated Th1 cells to the eye.…”
Section: Discussionsupporting
confidence: 92%
“…36,37 The CD4/CD8 ratio of T cells infiltrating the vitreous is elevated in ocular sarcoidosis compared with other etiologies of uveitis, 38 and T-cell clones established from the vitreous T cells of ocular sarcoidosis patients produce a large amount of inflammatory cytokines including IL-1a, IL-6, and IL-8. 39 Nagata et al 40 reported that vitreous levels of IL-1ra, IL-4, IL-5, IL-6, IL-8, IL-9, IL10, IL-12, IFN-c, and TNFa were elevated in ocular sarcoidosis patients compared with idiopathic ERM patients. In the present study, although there was no significant difference in vitreous IL-4 level between the ocular sarcoidosis group and the idiopathic ERM group, vitreous levels of IL-6, IL-10, IFN-c, and TNFa were significantly elevated in the ocular sarcoidosis group compared with the idiopathic ERM group (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have confirmation of our data in that at least some of our measured vitreal cytokine levels show levels that are comparable to already published data using the Bio-Plex technique (i.e., for IL-1b, IL-4, IL-8, and TNF-a). 15,21,22 Vitreomacular interface disorders, such as vitreomacular traction, can result in the formation of MHs. The persistence of such a disturbance can lead to the growth of ERMs, which may or may not be associated with the formation of MHs.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ alters the antigenicity of RPE cells, activates and recruits leukocytes, and magnifies local inflammatory responses in the outer retina [25,26,27]. Analysis of cytokine levels and macular thickness revealed that IFN-γ was significantly upregulated in patients with thin cystoid macular edema in sarcoidosis [28]. From previous reports, the upregulation of IFN-γ may lead to antiangiogenesis [15].…”
Section: Discussionmentioning
confidence: 99%